Enhancing User Experience Through Multi-touch: A Study on Multi-modal Human-Machine Interaction Interface Design - Moore, Ashley (Journal of Computer Science and Software Applications, 2024)
User experience is a pivotal element shaping users’ perceptions of a product, with interaction functionality playing a significant role in determining the quality of this experience. Compared to conventional single-finger touch operations, multi-touch interfaces are more adept at fulfilling user needs. This paper starts by defining human-computer interaction and proceeds with an in-depth analysis and study of the design of multi-modal human-machine interaction interfaces based on multitouch technology.